2019
DOI: 10.3390/electronics8121518
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Performance Evaluation of Various GNSS Receivers and Positioning Modes with Only One Flight Test

Abstract: The performance of global navigation satellite system (GNSS) receivers in dynamic modes is mostly assessed using results obtained from independent maneuvering of vehicles along similar trajectories at different times due to limitations of receivers, payload, space, and power of moving vehicles. However, such assessments do not ensure valid evaluation because the same GNSS signal environment cannot be ensured in a different test session irrespective of how accurately it mimics the original session. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In the 3 rd replication of receiver ID 7, with SBAS differential correction, there was a visible increase of E. In contrast, in the 4 th replication, E started with a high value and decreased over time. Lim et al (2019) described it as a factor associated with the need of providing the same signal environment to all receivers.…”
Section: Resultsmentioning
confidence: 99%
“…In the 3 rd replication of receiver ID 7, with SBAS differential correction, there was a visible increase of E. In contrast, in the 4 th replication, E started with a high value and decreased over time. Lim et al (2019) described it as a factor associated with the need of providing the same signal environment to all receivers.…”
Section: Resultsmentioning
confidence: 99%
“…The correction signal is usually received from a stationary RTK receiver, called a “base station”. It is possible to use a dedicated base station [ 1 , 29 ] or to rent corrections from a base station of the built RTK correction network without the need to build a new one [ 26 ]. The base station must be located several kilometres from the RTK receiver.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment results showed that, in the given test environment, the three-dimension precision of the relative positioning under open sky conditions was within 0.02 m. However, the study presented an evaluation of data from only two short periods of time (both approximately 6 min), where the movement speed of the measuring platform was given as approximately 5.5 m s −1 without specifying the definition of the acceleration performed. The evaluation of four RTK receivers against a postprocessed trajectory with a stated accuracy of 0.005 m was described by the authors of reference [ 26 ]. Among other things, this study provided specific values describing the accuracies depending on the artificially induced delay of the correction signal.…”
Section: Introductionmentioning
confidence: 99%
“…After acquiring all the GNSS signals and SBAS correction, we constructed a GNSS signal reradiation facility, as shown in Figure 13. We were able to replay the real time process of the online SBAS and SBAStoRTCM module by feeding a timely correction message to the system using the method presented in our previous study [34]. As shown in Figure 8, Pola RX and EVK-6 were set to the SBAS mode and received the signals reradiated from Labsat, and the other EVK-6 was connected to the SBAStoRTCM module to operate in the DGPS mode.…”
Section: System Configurationmentioning
confidence: 99%